Recurrence of Solid Pseudopapillary Tumor: A Rare Pancreatic Tumor - Chandra Punch; Nupur Garg; Penelope Harris (Case Reports in Oncological Medicine)
Solid pseudopapillary tumor of the pancreas (SPTP) is a rare disease of young females that does not usually recur after resection. Here we report a case of an elderly female with history of SPTP ten years ago who presented with anorexia and a palpable left lower quadrant abdominal mass. Imaging revealed metastatic disease and US-guided biopsy of the liver confirmed the diagnosis of SPTP. Due to her advanced age and comorbidities, she elected to undergo hospice care. The objective of this case report is to increase awareness of this tumor and its possibility of recurrence, necessitating further guidelines for follow-up.